Simulation of Cutting Force During High Speed End Milling of Inconel 718 - Ganesan, H. N.; Kasim, M. S.; Izamshah, R.; Anand, T.J.S.; Harun, N. H.; Sundi, S.A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This study aims to investigate the effect of cutting parameters on cutting force by simulation of high speed end milling of Inconel 718. The simulations were carried out using Deform 3D software. TiAlN/AlCrN-coated carbide inserts were employed as the cutting tool for the machining simulation. The milling cutting parameters were cutting speed (100-140 m/min), feed rate (0.1-0.2 mm/tooth) and axial depth of cut (0.5 – 1.0 mm). Response surface methodology (RSM) was used to determine the optimum cutting parameter in order to yield minimum cutting force. The minimum cutting force reported was 38.89 N, under the optimal parameter settings of Vc = 120.58 m/min, fz = 0.13mm/tooth and ap = 0.98mm.